Pengaruh Panjang Serat Pelepah Kelapa Sawit Terhadap Sifat Mekanik Bio Komposit dengan Resin Polyester - Fynnisa Z; Moraida Hasanah; Rahmadsyah Rahmadsyah; T Jukdin Saktisahdan; Ali Hasimi Pane; M Hafiz Tiannur (Universitas Islam Raden Rahmat, Malang, 2024)
The research uses natural palm frond fibre as a matrix in making bio composite and polyester resin as a filler. Making the bio composite is compressed using a hotpress machine at a temperature of 70°C for 20 minutes with a pressure of 30 kg/m2. Fiber lengths (2, 4, 6, 8, and 10) cm. Parameters include physical properties testing (density, porosity, and water absorption), mechanical properties testing (compressive, tensile, and impact strength), and SEM. The test results for the optimum physical properties are 75%:25% with a palm frond fibre length of 10 cm, a density of 0.793 gr/cm3, a porosity of 0.134%, a water absorption capacity of 0.169% and a compressive strength value of 19.234 MPa, tensile strength of 725.95 MPa, impact 1.1262 J/mm2. SEM results show that bio composite meets the